Evolution and adaptation in pseudomonas aeruginosa biofilms driven by mismatch repair system-deficient mutators - Lujan, Adela Maria (2011)
Pseudomonas aeruginosa is an important opportunistic pathogen causing chronic airway infections, especially in cystic fibrosis (CF) patients. The majority of the CF patients acquire P. aeruginosa during early childhood, and most of them develop chronic infections resulting in severe lung disease, which are rarely eradicated despite intensive antibiotic therapy. Current knowledge indicates that three major adaptive strategies, biofilm development, phenotypic diversification, and mutator phenotypes [driven by a defective mismatch repair system (MRS)], play important roles in P. aeruginosa chronic infections, but the relationship between these strategies is still poorly understood. We have used the flow-cell biofilm model system to investigate the impact of the mutS associated mutator phenotype on development, dynamics, diversification and adaptation of P. aeruginosa biofilms. Through competition experiments we demonstrate for the first time that P. aeruginosa MRS-deficient mutators had enhanced adaptability over wild-type strains when grown in structured biofilms but not as planktonic cells. This advantage was associated with enhanced micro-colony development and increased rates of phenotypic diversification, evidenced by biofilm architecture features and by a wider range and proportion of morphotypic colony variants, respectively. Additionally, morphotypic variants generated in mutator biofilms showed increased competitiveness, providing further evidence for mutator-driven adaptive evolution in the biofilm mode of growth. This work helps to understand the basis for the specific high proportion and role of mutators in chronic infections, where P. aeruginosa develops in biofilm communities.